The stars my destination - Bester, Alfred; Eisenstein, Alex.; Eisenstein, Phyllis, 1946- (London : Gollanz, 2010)
After escaping to the planet of Terra, Merchant Marine Gully Foyle must use his limited skills to survive in deep space and protect a secret the could change the course of history.
Adult.
Adult
Keywords: Merchant marine -- Fiction; Survival -- Fiction; Merchant marine -- Fiction; Science fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Outer space -- Fiction; Outer space -- Fiction; Science fiction